Critical Psychology and the Problem of Mental Health - Nell, Victor (PINS-Psychology in Society, 2026)
In December 1977, Noam Chomsky delivered the Johan Huizinga lecture in Leiden, Holland, in memory of the man who wrote In the shadow of tomorrow (1935), and Homo Ludens (1938), and was held under arrest during the Nazi occupation of Holland. In the lecture, Chomsky cites The crisis of democracy, a document produced in the 1970s by the Trilateral Commission, a private organisation of the elites of the United States, Western Europe and Japan set up by David Rockefeller to urge "moderation in democracy".